The Correlation between Estimation of Cranial Capacity and Working Memory Capacity in Elementary Students in Surakarta - Sari, Reza Yunita; Wiyono, Nanang; Iryawan, Andri (Nexus Biomedika, 2015)
Background: In children, the increasing of cranial capacity and the maturation of working memory capacity happen. The increasing of cranial capacity is driven by the growth of brain. The growth and the maturation of brain will influence someoneâs intelligence. The working memory capacity is one of the most important domains of intelligence. This research aimed to determine the correlationÂ  between the estimation of cranial capacity and the working memory capacity. Methods: This research was a descriptive analytical study which used cross sectional approach. The subjects of this study were 5th grade students at Kristen Manahan Elementary School. This research was done in 36 males of students by measuring cranial capacity and doing Reading Span Test for measuring working memory capacity. The collected data were analyzed with the Saphiro Wilk Normality Test and the Pearson Correlation. Results: The result of analysis showed r = 0.367 and p = 0.027, which meant that there was weak-powered correlation between the estimation of cranial capacity and the working memory capacity in the elementary students in Surakarta and this correlation was statistically significant. Conclusions: From this research, it is concluded that there is statistically significant correlation between the estimation of cranial capacity and the working memory capacity in the elementary students in Surakarta (r = 0.367). Keywords: Estimation of cranial capacity; working memory capacity; elementary student